2019
DOI: 10.1007/s10798-019-09549-x
|View full text |Cite
|
Sign up to set email alerts
|

Coaching in design-based learning: a grounded theory approach to create a theoretical model and practical propositions

Abstract: The purpose of this study is to determine what good coaching during design-based learning (DBL) entails by integrating theoretical and practical perspectives on good coaching. For this purpose, a grounded theory approach was used. For the practical perspective, themes on good coaching were derived from a qualitative study on coaching by observing and interviewing teachers and students involved in a DBL project. For the theoretical perspective, we consulted and analyzed literature on scaffolding, feedback, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…We offered weekly structured contact moments that allow for individual flexibility (G. J. T. Bombaerts et al, 2018). Oral feedback was organized in weekly coaching sessions (van Diggelen et al, 2019) to support students to give meaning to the process they went through. The number of respondents was too small to perform cluster analysis in the way we did in this article, but the analysis showed that a redesign based on the cluster analysis led to results for the entire group that was significantly better for competence, autonomy, and intrinsic motivation compared to the classical approach (G. Bombaerts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We offered weekly structured contact moments that allow for individual flexibility (G. J. T. Bombaerts et al, 2018). Oral feedback was organized in weekly coaching sessions (van Diggelen et al, 2019) to support students to give meaning to the process they went through. The number of respondents was too small to perform cluster analysis in the way we did in this article, but the analysis showed that a redesign based on the cluster analysis led to results for the entire group that was significantly better for competence, autonomy, and intrinsic motivation compared to the classical approach (G. Bombaerts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the system of students giving two individual peer feedbacks and receiving about eight feedbacks for their group in return has shown very good results in other contexts (Bombaerts and Nickel 2017), the time allocated for feedback in this course was too short to give sufficient and qualitative feedback for students. A peer feedback cycle of uploading a first version, giving feedback and implementing the feedback needs time to lead to good coaching (Van Diggelen et al 2019). In a nine-week course, a maximum of two of these cycles seem really feasible.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, e-tutors who are responsible with overseeing the design process must possess talents that will benefit students, particularly in terms of instructional skill selection and application. According to Van Diggelen et al (2021), e-tutors are expected to select teaching and learning methodologies that support students in becoming creative and innovative thinkers and possessing relevant skills to conceptualize the design process. This concept is significant because Orbey and Erdogdu (2020) argued that the design process is a creative activity with some idiosyncrasies, such as intuition and logic, and that their roles in the design process are to demonstrate that they can work together to solve design challenges.…”
Section: Literature Reviewmentioning
confidence: 99%